Frying performance of palm olein fortified with α-tocopherol - Thed, S. T. (1995)
Palm olein, the major form of palm oil consumed and exported from Malaysia is widely used as a frying oil. At frying temperature, the unsaturated fatty acids present in the oil are susceptible to oxidation resulting in the development of rancid off-flavor, changes in color and viscosity, and nutritional damage. In addition to the losses in quality, oxidised products may pose potential health risk. Tocopherols are losses in quality, oxidised products may pose potential health risk. Tocopherols are antioxidants found naturally in palm oil, however, the total tocopherols content is reduced by 30-40% during refining. This study was therefore undertaken to evaluate the frying performance of palm olein fortified with different levels of α-tocopherol. The quality changes of palm olein fortified with 500ppm (T1) and 1000ppm (T2) of α-tocopherol during frying at 180c for 6 hr perday for 3 days were monitored. Thiobarbituric acid (TBA) values, free fatty acid (FFA) content, color and viscosity of the oleins were determined. Sensory evaluation of the banana chips fried in these oils was also conducted. The added α-tocopherol significantly (α=0.05) decreased oxidative and hydrolytic deterioration of palm olein during frying. At the end of frying period, TBA values were 20.2, 14.3 and 8.4 umoles malonaldehydes/kg oil, while FFA were 0.72; 0.61 and 0.55% for control, T1 and T2 olein samples, respectively. Compared to the control olein, color intensity of fortified oleins increased more slowly but viscosity increased more rapidly. The concentrations of α-tocopherol used in this study did not significantly affect the overall acceptability of the fried banana chips.